Islamic Social Finance as a Pillar of Sustainable Economic Development: A Comparative Study of Zakat and Waqf Governance across Countries - Robi Firnando; Ali Sajad; Euis Amalia; Nisrina Mutiara Dewi (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2026)
Purpose – This study aims to map, compare, and analyze the variations in regulatory architectures and governance models of Islamic social finance (zakat and waqf) across six distinct jurisdictions: Indonesia, Malaysia, Saudi Arabia, Turkey, Singapore, and Thailand. Furthermore, this research integrates the governance of these instruments with the achievement of the Sustainable Development Goals (SDGs) Method – This study employs a qualitative approach with a descriptive-analytical design utilizing a comparative study method. The research data are derived from primary sources, specifically formal legal documents and regulations currently in force within each studied jurisdiction. These primary data are supplemented by secondary data obtained through library research, encompassing scientific literature, journal articles, historical documents, and contemporary institutional macro-statistical data.. Result – The findings reveal significant variations in the regulatory and institutional models of Islamic social finance across these nations; however, they all converge toward the same objectives: wealth redistribution, poverty alleviation, and the economic empowerment of the ummah. Productive waqf is shown to successfully transform stagnant assets into sustainable social investment instruments. Furthermore, integrating Zakat and Waqf into the Sustainable Development Goals (SDGs) framework strengthens the relevance of Islamic social finance as an instrument for inclusive development. Implication –This study implies that the strategic convergence of zakat and productive waqf serves as a pivotal pillar in accelerating SDG targets, particularly in eradicating poverty (SDG 1), ensuring food security (SDG 2), broadening access to quality education (SDG 4), stimulating economic growth (SDG 8), and reducing socio-economic inequalities (SDG 10).